2021
DOI: 10.1007/s11538-021-00946-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Research on an Immuno-Epidemiological Coupled System with Coinfection

Abstract: In this paper, a two-strain model with coinfection that links immunological and epidemiological dynamics across scales is formulated. On the with-in host scale, the two strains eliminate each other with the strain having the larger immunological reproduction number persisting. However, on the population scale coinfection is a common occurrence. Individuals infected with strain one can become coinfected with strain two and similarly for individuals originally infected with strain two. The immunological reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Similar strategy was used in another mathematical model with coinfection (Li et al. 2021 ). Gao et al studied a general coinfection model with bilinear incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Similar strategy was used in another mathematical model with coinfection (Li et al. 2021 ). Gao et al studied a general coinfection model with bilinear incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-strain mathematical models have been widely used to investigate the infectious disease dynamics ( Massard et al, 2022 , de León et al, 2022 , Li et al, 2021b , Rong et al, 2007 , Rong et al, 2012 , Li et al, 2021a , Li et al, 2013 , Martcheva, 2009 , Li et al, 2010 , Saucedo and Martcheva, 2017 , Dang et al, 2016 , Duan et al, 2018 , Cai et al, 2013 , Martcheva and Li, 2013 , Martcheva, 2007 , Thomasey and Martcheva, 2008 , Iannelli et al, 2005 , Martcheva et al, 2007 , Martcheva and Pilyugin, 2006 , Qiu et al, 2013 , Martcheva et al, 2008 , Arruda et al, 2021 , Fudolig and Howard, 2020 , Murall et al, 2014 , Poolman et al, 2008 ). Most studied the existence and stability of the disease-free equilibrium (DFE), strain-dominant equilibria and coexistence equilibria.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that plenty of diverse genetic variants can be coexisting in vivo in many viral infections, which would lead to more virulent infections [26]. Some two-strain coupled models have been studied which do not link the interaction between contaminated environment and virus in body [27,28]. Li et al [28] proposed a class of two-strain coinfection coupled model, which mainly focused on the coexistence equilibrium of two strains and the influence of within-host parameters on dynamics between host.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, most of the multi-strain transmission models assumed that the interaction between two strains is competitive [6,12,27,28]. However, it has been found that the relationship between various strains of pathogen is not only competitive, but also mutualistic, where one variant acts as a helper virus for the other in the latter [29,30].…”
Section: Introductionmentioning
confidence: 99%